Livelihood training, food production, and food security among vulnerable communities in Bangladesh - Andy Tran; Theresa Fang; Beryl Oranga; Ryan Kopper; Yunhee Kang (Agriculture & Food Security)
Abstract Objectives Massive influx of Rohingya refugees increases the risk of food insecurity in host communities in Bangladesh. This study explores intervention-related factors associated with food insecurity in the Bangladesh host households living near Rohingya refugees. Methods This secondary data analysis used the endline survey data from 660 host households who participated in the World Vision US Emergency Food System Security Project from 2019 to 2021. Logistic regression analysis was performed to explore the associations between program interventions and household dietary diversity score [HDDS: low (≤ 8) vs high (> 8)] and reduced coping strategy index [rCSI: high (> 3) vs. low (≤ 3)]. Results A total of 64.7% of households (n = 427) had low HDDS, and 10.6% (n = 70) had high rCSI. Purchasing food using cash transfer was associated with higher odds of high rCSI (adjusted odds ratio [AOR] = 2.10; 95% CI 1.25–3.53) and low HDDS (AOR = 1.57; 95% CI 1.13–2.18). Those who received food aid had higher odds of low HDDS (AOR = 3.16; 95% CI 1.69–5.89). Participants who farmed had lower odds of having high rCSI and low HDDS [AOR = 0.41 (95% CI 0.21–0.77) and AOR = 0.57 (95% CI 0.34–0.98), respectively]. Conclusion Our findings suggest that interventions focused on livelihood or farming training may yield the greatest reduction in food insecurity among host communities experiencing refugee influx. Humanitarian organizations should consider interventions that develop these farming skills over direct cash or food transfers to promote long-term self-sufficiency in the host population.